HARTA PERPANTANGAN SEBAGAI LIVING LAW MASYARAKAT BANJAR (Analisis Normatif-Empiris Terhadap Asal-Usul dan Praktik Pembagiannya) - Devi Kasumawati; Ahmad Manfaluti (JURNAL HAKAM, 2026)
Prohibited property is a concept of joint ownership between husband and wife in the Banjar community tradition that still functions as a living law even though it is not written in formal regulations or in the classical fiqh works of Sheikh Muhammad Arsyad al-Banjari. This study aims to trace the origins of the concept of perpantangan and examine the practice of its distribution through normative-empirical analysis. The research method used is qualitative with normative and empirical approaches. Primary data was obtained through interviews with juriyat (ulama descendants of Sheikh Arsyad), academics, and Banjar people who practice perpantangan, while secondary data were collected from fiqh literature, customary law, and national regulations. The results of the study indicate that perpantangan arose from social practices of the Banjar community since the 18th century as a response to the significant economic role of women in the household. Although no authentic manuscripts were found explaining this concept, the community legitimized the perpantangan to Sheikh Arsyad through cultural legitimacy mechanisms. Normatively, abstinence aligns with the principles of 'urf, syirkah al-abdan, and maslahah mursalah, so it does not conflict with muamalah jurisprudence or national law on joint property. Empirically, abstinence is practiced in a relatively uniform pattern, namely a 50% distribution for the surviving spouse and 50% as inheritance. This research confirms that abstinence is a form of articulation of the Banjar community's legal code of life that serves to maintain fair distribution of property within the family and represents a harmony between custom and sharia.